Emotional impact on pedagogy students faced with abuse during professional practice - Jaramillo Sandoval, Denisse Alejandra (2015)
The objective of this study was to understand the emotional experience of pedagogy students faced with abusive events caused by teachers of the institution during their professional practice. From the qualitative approach, and using the critical incidents technique, we interviewed 12 students who experienced abuse during their practice and gathered 15 critical incidents. From this sample, it was categorized 5 abusive behaviors of which anguish, anger, and insecurity were the main emotions expressed by the students. For them, such experience had an intense emotional impact associating it with high levels of stress. The discussion that these events caused them to significantly question in their professional identity; and on the other hand, regarding the importance of strengthening the socio-emotional skills in teacher training, so that conflicts are managed properly – thereby maintaining the psychological well-being.